Electrochemical behaviour of myoglobin at an array of microscopic liquid–liquid interfaces - O'Sullivan, S.; Arrigan, Damien (Pergamon, 2012)
Electrochemistry at liquid–liquid interfaces, or at interfaces between two immiscible electrolyte solutions ITIES, provides a basis for the non-redox detection of biological molecules, based on ion-transferor adsorption processes. The electroactivity of myoglobin at an array of micron-sized liquid–organogel interfaces was investigated. The μITIES array was patterned with a silicon membrane consisting of an array of eight pores with radii of ~12.8 μm and a pore to pore separation of ~400 μm. Using cyclic voltammetry at the ITIES, the protein was shown to adsorb at the interface and facilitate the transfer of the organic phase electrolyte anions to the aqueous side of the interface. The electrochemical current response was linear with concentration in the range of 1–6 μM, with corresponding surface coverage of 10–50 pmol cm-2. The reverse peak currents was found to be proportional to the voltammetric scan rate, indicating a desorption process. The detection of the protein was only possibly when the pH of the aqueous phase solution was below the pI of the protein. The steady-state simple ion transfer behaviour of tetraethylammonium cation was decreased on the forward sweep, providing a qualitative indication of the presence of adsorbed protein at the interface. Increasing the ionic strength of the aqueous phase resulted in enhanced peak currents, possibly due to aggregation of protein precipitates in the aqueous solution. UV/Vis absorbance spectroscopy was used to investigate the effects of various aqueous electrolyte solutions on the structure of the protein, and it was shown that at low pH the protein is at least partially denatured. These results provide the basis for label-free detection of myoglobin at the ITIES.